Convergence of educational technologies as an imperative for the development of innovation cooperation in the context of circular transformation - Prokhorova, Viktoriia; Mushnykova, Svitlana; Kovalenko, Denys; Koleshchuk, Orest; Babichev, Anatoliy (Eastern-European Journal of Enterprise Technologies, 2023)
The object of the study is the process of convergence of educational technologies as an imperative for the development of innovative cooperation under the conditions of circular transformation. The central element of circular transformations is a person who must quickly react and adapt to changes in the external environment and solve management problems through systematic professional growth. This can be achieved thanks to the introduction of high-quality modern educational technologies, which require both special knowledge of the theory and practice of management, as well as personal development qualities. To achieve a state of sustainable development, managers making management decisions must quickly respond and adapt to changes in the external environment to solve various management problems. This requires systematic professional growth through the transition to high-quality new educational technologies. Combining the principles of global cooperation, defining the key imperatives of sustainable development and finding innovative measures of cooperation under the renewed conditions of the circular economy must be based on education. The main generally accepted indicator of the level of development of any country in the world is GDP. But under conditions of uncertainty and change, the real state of development and progress can be determined using the Genuine Progress Indicator (GPI), which is an integral indicator. One of the main issues is the determination of the level of sustainable development in the context of circular transformations, taking into account the influence of the level of education and existing approaches to its assessment. If we take into account that the conditions for cyclical transformations must occur, including through raising the level of education and the constant transfer of education into practice, then the inclusion of the Index of the level of education is necessary to calculate the real state of development of any country